Efektivitas Penggunaan Aplikasi Kahoot dalam Meningkatkan Motivasi Belajar Siswa Sekolah Dasar: Studi Literatur - Rahmawati, Iin Nur Indah; Uliya, Nurul Manzilatul; Susilawati, Samsul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
In recent years, the development of information technology has brought significant changes to the field of education. One noteworthy innovation is the use of gamification applications like Kahoot, which aim to enhance interactivity and student engagement in the learning process. This study aims to analyze the effectiveness of using the Kahoot application in increasing elementary school students' motivation to learn. Using a qualitative method, data were collected through literature reviews and online searches. The results of the study indicate that the Kahoot application is effective in increasing elementary school students' motivation to learn. Several supporting factors were identified, including attractive visual displays, immediate feedback, and a healthy competitive atmosphere. However, there are also inhibiting factors such as limited access to technology and teachers' readiness to integrate this application into the curriculum. The implications of this study suggest that using Kahoot can increase student engagement and provide an enjoyable learning experience. This study is expected to provide practical guidance for educators in implementing gamification technology to enhance student motivation. Additionally, this research encourages further studies to explore the effectiveness of this application in various educational contexts.